Determinants of maximal whole‐body fat oxidation in elite cross‐country skiers: Role of skeletal muscle mitochondria. (4th October 2018) - Dandanell, Sune; Meinild‐Lundby, Anne‐Kristine; Andersen, Andreas B.; Lang, Paul F.; Oberholzer, Laura; Keiser, Stefanie; Robach, Paul; Larsen, Steen; Rønnestad, Bent R.; Lundby, Carsten
Abstract: Elite endurance athletes possess a high capacity for whole‐body maximal fat oxidation (MFO). The aim was to investigate the determinants of a high MFO in endurance athletes. The hypotheses were that augmented MFO in endurance athletes is related to concomitantly increments of skeletal muscle mitochondrial volume density (MitoVD ) and mitochondrial fatty acid oxidation (FAO p ), that is, quantitative mitochondrial adaptations as well as intrinsic FAO p per mitochondria, that is, qualitative adaptations. Eight competitive male cross‐country skiers and eight untrained controls were compared in the study. A graded exercise test was performed to determine MFO, the intensity where MFO occurs (FatMax ), and V ˙ O 2 Max . Skeletal muscle biopsies were obtained to determine MitoVD (electron microscopy), FAO p, and OXPHOS p (high‐resolution respirometry). The following were higher ( P < 0.05) in endurance athletes compared to controls: MFO (mean [95% confidence intervals]) (0.60 g/min [0.50‐0.70] vs 0.32 [0.24‐0.39]), FatMax (46% V ˙ O 2 Max [44‐47] vs 35 [34‐37]), V ˙ O 2 Max (71 mL/min/kg [69‐72] vs 48 [47‐49]), MitoVD (7.8% [7.2‐8.5] vs 6.0 [5.3‐6.8]), FAO p (34 pmol/s/mg muscle ww [27‐40] vs 21 [17‐25]), and OXPHOS p (108 pmol/s/mg muscle ww [104‐112] vs 69 [68‐71]). Intrinsic FAO p (4.0 pmol/s/mg muscle w.w/MitoVD [2.7‐5.3] vs 3.3 [2.7‐3.9]) and OXPHOS p (14 pmol/s/mg muscle ww/MitoVD [13‐15] vs 11 [10‐13]) were, however, similar in the endurance athletes and untrained controls. MFO and MitoVD correlated ( r 2 = 0.504, P < 0.05) in the endurance athletes. A strong correlation between MitoVD and MFO suggests that expansion of MitoVD might be rate‐limiting for MFO in the endurance athletes. In contrast, intrinsic mitochondrial changes were not associated with augmented MFO.